2012
DOI: 10.1016/j.jcrs.2011.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Riboflavin injection into the corneal channel for combined collagen crosslinking and intrastromal corneal ring segment implantation

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(44 citation statements)
references
References 21 publications
3
41
0
Order By: Relevance
“…Currently, ICRS is mostly used in patients with keratoconus [2] and is becoming a popular alternative for the treatment of post-LASIK ectasia. ICRS can be used alone or in combination with other techniques, such as corneal collagen cross-linking (CXL) to improve vision [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, ICRS is mostly used in patients with keratoconus [2] and is becoming a popular alternative for the treatment of post-LASIK ectasia. ICRS can be used alone or in combination with other techniques, such as corneal collagen cross-linking (CXL) to improve vision [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…7 Kılıç et al proposed a technique for riboflavin application without epithelial removal. 26 In this technique, patients underwent combined CXL and ICRS and simultaneous transepithelial CXL with riboflavin injection into the corneal channel (Figs 2 and 3). …”
Section: Simultaneous Treatment With Intracorneal Riboflavin Injectionmentioning
confidence: 99%
“…This may be related to the unpredictable refractive outcomes when excimer ablation is performed on cross-linked tissues. However, performing both procedures concurrently on the same day may cause an irregular healing process with the formation of persistent stromal haze, probably related to keratocyte activation, which permanently affects visual performance 95,96 .…”
Section: Combined Treatmentmentioning
confidence: 99%
“…Moreover, it was reported that after one or both ring explantations, the refractive effects may be stable or reversible while the topographic changes seem to be maintained [96][97][98][99] . Therefore, while collagen crosslinking can be performed before, in conjunction with, or after ICRS implantation, the ideal method for combining these two treatments is still undefined.…”
Section: And Intracorneal Ringsmentioning
confidence: 99%